Analisis Faktor yang Berhubungan dengan Status Gizi pada Remaja Putri di SMAN 28 Jakarta - Juneth Sara Mahligay Latubual; Aisyiah Aisyiah; Tommy Wowor (Malahayati Nursing Journal, 2023)
ABSTRACT The nutritional problems that often occur in adolescents today are undernutrition and overnutrition. Malnutrition in adolescents can cause a decrease in body resistance so that it is susceptible to infectious diseases, while excess nutrition can cause obesity which is susceptible to various degenerative diseases such as diabetes, high blood pressure and coronary heart disease. This study aims to determine the factors associated with the nutritional status of young women at SMAN 28 Jakarta. Analytical descriptive study using a cross sectional approach. The sample in this study amounted to 96 samples. The sampling technique used purposive sampling. The research instrument consisted of body image questionnaires, eating patterns, knowledge and behavior of snacks. Questionnaire of nutritional knowledge and snacking behavior has been tested for validity and reliability with a value of Cronbach's alpha coefficient of nutritional knowledge of 0.784 and snacking behavior of 0.791. Data were analyzed using chi square to determine the relationship between body image, eating patterns, knowledge and behavior of snacks with nutritional status. The results showed that there was a relationship between body image and nutritional status (p value 0.011), there was a relationship between diet and nutritional status (p value 0.020), there was a relationship between snacking behavior and nutritional status (p value 0.047) and there was no relationship between knowledge and nutritional status (p value 0.54).  Body image, eating patterns and snacking behavior are related to nutritional status, while knowledge is not related to nutritional status. Keywords: Body Image, Diet, Knowledge, Nutritional Status, Snacking Behavior, Young Women.   ABSTRAK Masalah gizi yang sering terjadi pada remaja saat ini adalah kekurangan gizi (undernutrion) dan kelebihan gizi (overnutrion). Kekurangan gizi pada remaja dapat menyebabkan penurunan daya tahan tubuh sehingga rentan terhadap infeksi penyakit, sedangkan kelebihan gizi dapat menyebabkan obesitas yang rentan terhadap berbagai penyakit degeneratif seperti diabetes, tekanan darah tinggi dan jantung koroner. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan status gizi pada remaja putri di SMAN 28 Jakarta. Penelitian deskriptif analitik menggunakan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 96 sampel. Teknik pengambilan sampel menggunakan purposive sampling. Instrumen penelitian terdiri dari kuesioner body image, pola makan, pengetahuan dan perilaku jajan. Kuesioner pengetahuan gizi dan perilaku jajan telah diuji validitas dan reabilitas dengan nilai koefisien cronbach’s alpha pengetahuan gizi 0,784 dan perilaku jajan 0,791. Data dianalisis menggunakan chi square untuk mengetahui hubungan antara body image, pola makan, pengetahuan dan perilaku jajan dengan status gizi. Hasil penelitian menunjukan terdapat hubungan antara body image dengan status gizi (p value 0,011), terdapat hubungan antara pola makan dengan status gizi (p value 0,020), terdapat hubungan antara perilaku jajan dengan status gizi (p value 0,047) dan tidak terdapat hubungan antara pengetahuan dengan status gizi (p value 0,54). Body image, pola makan dan perilaku jajan berhubungan dengan status gizi, sedangkan pengetahuan tidak berhubungan dengan status gizi. Kata Kunci : Body Image, Pengetahuan, Perilaku Jajan, Pola Makan, Remaja Putri, Status Gizi.